Sistem Pendukung Keputusan Pemilihan Jurusan di STMIK Bina Patria Magelang - deftandhi, Vaisa; Faris Setiadi, Yoga; Kurniawan, Danang (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Choosing a college major is an important decision that can significantly impact a student's career and future. This study aims to assist prospective students in selecting the most suitable major at STMIK Bina Patria using the Simple Additive Weighting (SAW) method. The three majors evaluated in this study are Computer Engineering, Information Systems, and Management Informatics. The SAW method is used to process several relevant criteria in the major selection process, including personal interest, job prospects, availability of facilities, tuition fees, and study duration. Each criterion is assigned a specific weight, and the evaluation is carried out for the three majors based on the scores obtained from each criterion. The calculation results indicate that the Computer Engineering major received the highest score, followed by Management Informatics and Information Systems. This study provides recommendations for prospective students to consider the factors that have been analyzed when selecting a major that aligns with their preferences and career goals. Therefore, the SAW method can be used as a tool to support more objective and structured decision-making in the college major selection process at STMIK Bina Patria.